Microstructures and Dehydrogenation Properties of Ball-milled MgH2-K2Ti6O13-Ni Composite Systems - ZHANG Jian; TANG Wang; SHAO Lei; YU Xiao-feng; LONG Chun-guang; CHEN Jian (Cailiao gongcheng, 2016)
The K2Ti6O13 whisker separate-doped and K2Ti6O13 whisker and Ni powder multi-doped MgH2 hydrogen storage composite systems were prepared by mechanical milling method. The microstructures and dehydrogenation properties of the prepared samples were characterized by some testing methods such as X-ray diffraction (XRD), scanning electron microscope (SEM) and differential scanning calorimeter (DSC). The results show that the K2Ti6O13 whisker not only plays the roles in refining the MgH2 crystalline grain, but also inhibit the agglomeration of MgH2 particles in K2Ti6O13 whisker separate-doped system, which results in the decreased dehydrogenation temperature of MgH2 matrix. When the mass ratio of K2Ti6O13 to MgH2 is 3:7, the improvement effect on dehydrogenation properties of MgH2 is the most remarkable. As compared with pure ball-milled MgH2, the dehydrogenation temperature of MgH2 in K2Ti6O13 whisker separate-doped system is decreased by nearly 75℃. For K2Ti6O13 whisker and Ni powder multi-dopedsystem, the dehydrogenation temperature of MgH2 matrix is further decreased compared to K2Ti6O13 whisker separate-doped one due to the dual effects of refined MgH2 crystalline grain by K2Ti6O13 whisker and destabilized MgH2 lattice by Ni solution. As compared with pure ball-milled MgH2, the dehydrogenation temperature of MgH2 in K2Ti6O13 whisker and Ni powder multi-doped system is decreased by nearly 87℃.